Production and Purification of Filovirus Glycoproteins in Insect and Mammalian Cell Lines. Issue 1 (December 2017) - Clarke, Elizabeth; Collar, Amanda; Ye, Chunyan; Caì, Yíngyún; Anaya, Eduardo; Rinaldi, Derek; Martinez, Britney; Yarborough, Sarah; Merle, Christine; Theisen, Manfred; Wada, Jiro; Kuhn, Jens; et al.
Abstract Filoviruses are highly virulent pathogens capable of causing severe disease. The glycoproteins of filoviruses are the only virally expressed proteins on the virion surface and are required for receptor binding. As such, they are the main candidate vaccine antigen. Despite their virulence, most filoviruses are not comprehensively characterized, and relatively few commercially produced reagents are available for their study. Here, we describe two methods for production and purification of filovirus glycoproteins in insect and mammalian cell lines. Considerations of expression vector choice, modifications to sequence, troubleshooting of purification method, and glycosylation differences are all important for successful expression of filovirus glycoproteins in cell lines. Given the scarcity of commercially available filovirus glycoproteins, we hope our experiences with possible difficulties in purification of the proteins will facilitate other researchers to produce and purify filovirus glycoproteins rapidly.